Stress levels in family members of patients with covid-19, Tayacaja, Huancavelica - Acosta-Román, Mercedes (2022)
Objective of the research is to determine the level of stress that was caused in relatives of patients with Covid-19 in the province of Tayacaja. Methodology: The Hamilton Stress Test was used as an instrument, which is already validated and used in countless research works. This instrument comprised two parts: the first, general information about the interviewee was recorded; the second included information regarding mood disorder symptoms and psychosomatic reactions. This Test covers different physical and psychological states of the person, such as: pains, discomforts, energy, moods, conciliation of sleep, among others. Regarding the responses, they determine with what intensity these symptoms appear. Results: Mood disorder, the sum of the mild, moderate and severe levels gives 79% of stress; Psychosomatic reactions, the addition of mild and moderate levels give a total of 73%. Young people in the age range between 18 to 29 years, present stress levels in a higher proportion (70%). Conclusions: The consolidation of the dimensions reveals the stress levels of the relatives of the patients with COVID-19, who show mild (61%), moderate (21%) and normal (18%) stress.